Adversity Quotient of the Probationary Faculty Members in Philippine State Universities (Region III) - Stefhan Angelo A Payad; Christian L Banal; Jennifer Victoria N Genato; Vladimir B Villejo; May D Borja; Mark Jay P Asutilla (Applied Quantitative Analysis, 2026)
This research investigated Paul Stoltz’s Adversity Quotient (AQ) among probationary faculty members across selected state universities in the Philippines. The study aimed to assess their AQ profile across the CORE dimensions of Control, Ownership, Reach, and Endurance and to determine the relationship between selected demographic variables and AQ. Using a descriptive-correlational research design, data were collected from 100 respondents selected using Yamane’s formula through employing the Adversity Quotient Profile (AQP). Pearson’s product-moment correlation, point-biserial correlation, and Spearman’s rank-order correlation were used according to the measurement level of the variables. Results indicated that the average respondent was 28 years old, predominantly male, held a bachelor’s degree, and had three years of service. Participants generally exhibited moderate levels of control, ownership, and endurance but scored below average in reach, resulting in an overall average AQ. Correlational analyses indicated that none of the selected demographic variables, namely age, sex, length of service, and educational attainment, were significantly associated with the Adversity Quotient (AQ) of probationary faculty members. The findings suggest that probationary faculty members generally demonstrated an average level of Adversity Quotient, indicating a moderate capacity to cope with workplace challenges. Although no significant relationships were found between the selected demographic variables and AQ, the study highlights the value of fostering resilience and adaptive coping through faculty development initiatives. These findings offer practical insights for higher education institutions in designing mentoring, wellness, and professional development programs that support faculty well-being and sustained professional engagement.